Searching for synergies for low emission development, the case for dairy subsector in Kenya - Onyango, J.; Vellema, S.; Crane, Todd A.; Atela, J. (Springer, 2024)
This research paper assesses the coherence of policy measures and documents related to low emission dairy development (LEDD) initiatives at different levels with a focus on Kenya. To analyse coherence, an innovative stepwise approach was employed including sampling of measures, assessing for vertical and horizontal coherences, and detecting areas of synergies for prioritisation of measures. Six international level documents, six national level sectoral documents, and two local level documents were analysed to extract a total of 145 measures. These measures were then thematically coded and assessed for coherence with LEDD. The findings reveal that while some policy documents reinforce and enable each other, others show limited coherence in supporting LEDD. The study highlights the importance of classifying coherence among measures and documents to prioritise options for policy makers. The paper identified four key documents as strategic for reinforcing LEDD measures across other policy measures comprising the Kenya Green Economy Strategy and Implementation Plan (KGESIP), the Medium Term Three Big Four Agenda (B4A), the SDGs (Sustainable Development Goals), and the World Bank Climate Smart Agriculture (WB CSA). The paper identifies that policy documents structured to support implementation at the local level tend to be more synergistic. Further, the paper identifies that measures which provide forward-looking pathways, and builds agency among stakeholders, are likely to promote synergistic coherence. This paper contributes to the existing body of knowledge by shedding light on the level of coherence among policy measures and documents in the context of sustainable agriculture in Kenya. It provides insights and recommendations to facilitate effective implementation of LEDD initiatives at national and local levels.